From nanoengineering to nanomedicine: A facile route to enhance biocompatibility of graphene as a potential nano-carrier for targeted drug delivery using natural deep eutectic solvents. (23rd February 2019) - Zainal-Abidin, Mohamad Hamdi; Hayyan, Maan; Ngoh, Gek Cheng; Wong, Won Fen
Graphical abstract: Highlights: Recently, graphene has been intensively studied as a promising drug nano-carrier. However, graphene is deemed to be potentially toxic to humans and to environment. In this work, a novel route was used to enhance graphene biocompatibility. Natural deep eutectic solvents were implemented as promising functionalizing agents. Tamoxifen was successfully loaded on the functionalized graphene for cancer therapy. Abstract: Graphene has attracted massive interest in numerous biomedical applications such as anti-cancer therapy, drug delivery, bio-imaging and gene delivery. Therefore, it is important to ensure that graphene is nontoxic, and that its cellular biological behavior is safe and biocompatible. Herein, a new route was used to enhance the biocompatibility of graphene, using several natural deep eutectic solvents (DESs) as functionalizing agents, owing to their capability to introduce various functional groups and surface modifications. Characterization of the physicochemical changes in DES-functionalized graphene were conducted by FE-SEM, FTIR, XRD, and Raman spectroscopy. There were considerable improvements in the cytotoxicity profile of DES-functionalized graphene compared to pristine graphene and oxidized graphene, as demonstrated by cell viability, cell cycle progression, and reactive oxygen species evaluation assays. We also studied the association between cellular toxicity of DES-functionalized graphene and their physicochemical properties. To the best of our knowledge, this is the first study on the cytotoxicity profile improvement of graphene using DESs as functionalizing agents, and its cellular biological behavior. The application of DESs as functionalizing agents, especially for DES choline chloride (ChCl):malonic acid (1:1), significantly reduced the cytotoxicity level of graphenes. DES ChCl:malonic acid (1:1) also demonstrated higher tamoxifen entrapment efficiency and loading capacity in comparison to the functionalization with DES ChCl:glucose (2:1), ChCl:fructose (2:1) and ChCl:sucrose (2:1). Therefore, DES ChCl:malonic acid (1:1) is considered the most promising nano-carrier for drug delivery applications, owing to its lower cytotoxicity and higher drug loading capacity.